Kompleksowe zarządzanie należnościami nieregularnymi jako nowoczesna usługa finansowa - Półtorak, Bogusław (Receivables Management as an Innovative Financing Servic, 2007)
This paper discusses outsourcing in receivables management. In this process an important role as services play debt collection firms. The aim of their activities is to limit risk of financial liquidity, credit risks management and improve profitability ratios of their clients. In order to achieve that they use scope of operations: receivables monitoring, out-of-court collection, personal collection, court collection and enforcement collection, debt purchasing, detective services, management of non-standard cases and B2B receivables. Collection services are usually provided at no upfront cost to cooperation firms and the fee is based on results. Due to the innovative receivables management, safety of economic activities can rise in the whole national economy. In Polish market the bigger share have consumer receivables. In the future we can expect that B2B receivables services will be developed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 431-439